Effect of solvent mixture pretreatment on sugar release from short-rotation coppice Salix schwerinii for biobutanol production. (January 2022) - Yang, Ming; Guo, Xiaojun; Liu, Guozhen; Nan, Yufei; Zhang, Junhua; Noyazzesh, Hossain; Kuittinen, Suvi; Vepsäläinen, Jouko; Pappinen, Ari
Graphical abstract: Highlights: ABE pretreatment improved the sugar recovery from the S. schwerinii biomass . The ABE pretreatment effectively removed xylan and partial lignin from the biomass. ABE with a higher concentration tends to be lost when considering their recycle. The fermentation broth containing ABE was successfully employed for pretreatment. This study provides an effective method for lignocellulosic biomass fractionation. Abstract: This study investigated the effects of pretreatment using an acetone–butanol–ethanol (ABE) mixture with and without H2 SO4 (H + ) as a catalyst on sugar recovery from Salix schwerinii biomass. The sugar recovery was susceptible to both the temperature and the catalyst. Moreover, the relatively higher concentration of ABE (H + ABE4) at 200 °C yielded glucose recovery of 85.5% from the pretreated solid, higher than the recovery under other conditions. This result was mainly attributed to the compositional changes in the biomass, as the xylan and lignin were removed in large quantities by ABE pretreatment at 200 °C. Correspondingly, xylose recovery of 53.8% and glucose recovery of 12.1% were obtained from the liquid in which more sugar degradation products were formed. Ultimately, a fermentation broth containing a low concentration of ABE was successfully employed for pretreatment and showed great potential in producing fermentable sugars from S. schwerinii for biobutanol production.